Investigation of optical properties of dusty plasma in capacitive radio frequency discharge of argon - Slamiya, M.; Orazbayev, S.A.; Jumagulov, M.N.; Kabylkak, М.; Jumabekov, A.N.; Dosbolayev, M.K.; Ramazanov, T.S. (Recent Contributions to Physics, 2012)
In present paper the results of the experimental investigations of optical properties of dusty plasma in capacitive radio frequency discharge were presented. The influence of dust component on intensity of spectral lines was shown on the basis of analysis of spatial spectra of radiofrequency discharge plasma. Experiments for defining the emission intensity were carried out at different values of number density of dust particles and without them. Experiments have shown that with the increasing of number density of dust particles the emission intensity in the near-electrode regions increases and decreases with the decreasing of number density of dust particles. Results of present work can find the applications in modern technologies and also for investigating of other plasma properties.